Fatal cold agglutinin-induced haemolytic anaemia: a case report - Reverberi Roberto; Resca Daniela; Lodi Gianluca (Journal of Medical Case Reports, 2010)
Abstract Introduction Cold agglutinin disease usually develops as a result of the production of a specific immunoglobulin M auto-antibody directed against the I/i and H antigens, precursors of the ABH and Lewis blood group substances, on red blood cells. Autoimmune and lymphoproliferative disorders, Mycoplasma pneumoniae and other infections can be associated with the production of cold agglutinins. In its classic presentation with haemolytic anaemia and Raynaud's syndrome, cold agglutinin disease is usually idiopathic. Several factors play a role in determining the ability of a cold agglutinin to induce a haemolytic anaemia such as antibody concentration and temperature range, in particular the highest temperature at which antibodies interact with red blood cells. Case presentation A 48-year-old Caucasian man presented to our hospital with symptoms of extreme asthenia caused by severe anaemia. The transfusion of red blood cells (O Rh-positive), started as prescribed by the emergency guidelines in force without pre-transfusion tests, induced fatal haemolysis because of the presence of high levels of anti-H antibodies in his blood, that reacted with the large amount of H antigen in universal (0) red blood cells. Conclusion Emergency transfusion of universal red blood cells (0 Rh-positive or negative) is usually accepted by the international guidelines in force in emergency departments. In this report we describe a rare complication caused by the very high concentration in the recipient of cold agglutinins and the activation of the complement system, responsible for red blood cell lysis and consequent fatal cardiovascular shock. We conclude that emergency transfusion of universal red blood cells (0 Rh-positive or negative) may be dangerous and its risk should be assessed against the risk of delaying transfusion until the pre-transfusion tests are completed.